The educational and recreational role of the Scout camps and its relationship to the internal motivation of Iraqi universities' guides - Hadood Obaid, Watheq; Mohammed Hamzha, Salam; abdul kareem abdul yemmah, Qayssar (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the current research lies in showing the educational and recreational role of the scout camps and the positive outcomes that they can contribute to the participation of female students at the university level, especially with regard to their internal motivation to face the practical life after graduation, including its challenges.The current research aimed to find out the relationship and differences between the educational and recreational role of the scout camps and the internal motivation of the guides participating in the scout camps at the university level. The research sample included the 100 students participating in the scout camps.The researchers used the descriptive approach with the survey and correlational methods to know the educational and recreational role consisting of three main areas: education for social life, environmental education, and emotional education. And internal motivation consisting of three main areas: preference for challenge, curiosity, and the desire to master independently, as well as knowledge of the relationship between the two variables mentioned in the guides of Iraqi universities.The researchers concluded: The existence of a correlation between the educational and recreational role of the scout camps and the internal motivation of Iraqi universities' guides.The researchers recommended several recommendations, the most important of which are:Preparing advanced programs compatible with the standards of Iraqi universities' guides during the establishment of scout camps.Work to create desire and enthusiasm in the contribution of female university students to join the guide teams to maintain the basic tasks of the scout movement.